THE ROLE OF TECHNOLOGY IN SUPPORTING ENGLISH LEARNING IN ELEMENTARY SCHOOLS - Dwi Maryani Rispatiningsih (GoAcademica Research dan Publishing, 2022)
Currently, teachers face many challenges in teaching. This is due to the times, which causes a teacher to need to innovate in teaching methods. Learning to use technology is one of the steps that can be used by teachers in this era to be able to face these challenges, especially English teachers. This research will then be carried out using descriptive qualitative research. The data used in this study comes from the results of previous research and studies that still have relevance to the research content. The results of this study then found that learning English using multimedia technology can increase students’ motivation and interest in learning. Of course, this must be done by providing open access to teaching materials and information. In the future, multimedia technology will become more common as a learning aid. Even though there are still limitations in using technology in learning, with proper computer knowledge on the part of the teacher, learning using this technology can be carried out correctly.